The enabling technologies of industry 4.0: Examining the seeds of the fourth industrial revolution - Arianna Martinelli; Andrea Mina; Massimo Moggi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2019)
Technological revolutions mark profound transformations in socio-economic systems. They are associated with the diffusion of general purpose technologies that display very high degrees of pervasiveness, dynamism and complementarity. This paper provides an in-depth examination of the technologies underpinning the "factory of the future" as profiled by the Industry 4.0 paradigm. It contains an exploratory comparative analysis of the technological bases and the emergent patterns of development of Internet of Things (IoT), big data, cloud, robotics, artificial intelligence and additive manufacturing. By qualifying the "enabling" nature of these technologies, it explores to what extent their diffusion and convergence can be configured as the trigger of a fourth industrial revolution, and identifies key themes for future research on this topic from the viewpoint of industrial and corporate change.
Keywords: O33; O31; L01; 330; Industry 4.0; technological paradigm; enabling technology; general purpose technology; disruptive innovation